Inovasi Pembelajaran Matematika Permulaan Anak Usia Dini: Pelatihan Pengembangan Model Pembelajaran bagi Guru PAUD Kota Bandar Lampung - Nia Fatmawati; Nopiana Nopiana (Prodi PGSD Unsultra, 2025)
Early childhood education is an important foundation in building cognitive abilities, including early mathematics skills. However, many PAUD teachers in Bandar Lampung City still face difficulties in developing innovative and contextual mathematics learning models. This study aims to identify the effectiveness of early mathematics learning model development training for PAUD teachers and evaluate changes in their learning practices. The implementation method is participatory training and direct practice with a lesson study approach and collective reflection. This activity involved 30 PAUD teachers from various sub-districts in Bandar Lampung City. The results of the training showed that teachers experienced significant improvements in their ability to design mathematics learning based on games, the surrounding environment, and thematic approaches. Most participants admitted to being more confident and creative in delivering mathematics materials to early childhood. This finding shows that training that is applicative and collaborative can encourage learning innovations that are in accordance with the characteristics of early childhood. This article recommends the need for ongoing training involving practitioners, lecturers, and teacher learning communities to maintain the sustainability of learning innovations in PAUD.